Design of an Internet Of Things-Based Air Quality Monitoring Tool Using Microcontroller and MQ-135 Sensor - Tianto, Akbar Waqis; Ramandha, Raina Putri; Firdaus, Reikhan; Firmansyah, Zidan Inov; Arif Cahyono, Muhammad Ridwan (Teknik Elektro Universitas Siliwangi, 2025)
Poor air quality caused by industrial pollution poses a significant challenge for the Politeknik Gajah Tunggal campus, located in Tangerang's industrial area. To address this issue, this study developed an Internet of Things (IoT) based air quality monitoring device utilizing an Arduino Uno microcontroller, ESP-8266, and MQ 135 sensor. The device detects various pollutants, including CO, CO2, and other harmful gases, with real-time data displayed through a Kodular based application. Tests conducted under various air conditions demonstrated the device's high accuracy in pollutant detection. Indoor air tests recorded an average of 42 ppm (good category), while outdoor air tests averaged 48 ppm (good category). Exposure to cigarette lighter gas produced a maximum value of 880 ppm (severe category), and burning paper smoke yielded an average of 295 ppm (poor category). Consistency between the LED P10 display and the Kodular application results reached 100%. Overall, the device delivers quick and accurate air quality information, enhancing user awareness by up to 90%, as indicated by post-implementation surveys .